Using magnetic field analysis to evaluate the suitability of a magnetic suspension system for lightweight vehicles - Isa, H.M.; Amer, N.H.; Wan Mahadi, W.N.L.; Ramli, R. (Turkiye Klinikleri Journal of Medical Sciences, 2016)
A suspension system in a vehicle acts as an isolator that isolates vibrations between the wheel tires and the vehicle body due to road irregularities. Additionally, a suspension system serves as a vehicle stabilizer that stabilizes the vehicle body during unusual driving patterns such as cornering, braking, or accelerating. A controllable suspension system has received significant attention in the automotive world in previous years since it can perform both of the aforementioned tasks without the presence of uid damper. The study presented in this paper focuses on using magnetic ux density analysis to evaluate a number of parameters of an electromagnetic suspension system (EMS), so that it is suitable for usage in middle-sized passenger vehicles. The proposed EMS utilizes tubular linear actuator with a NdFeB permanent magnet. A number of dimensions of the EMS have been varied to observe their respective effect on force output and magnetic ux density. The purpose of this process was to determine what size of EMS will produce the same force as a standard suspension system, which has a maximum of 2000 N and an average of 800 N, according to quarter vehicle simulation that worked in parallel with this study.